Tomografia por emissão de pósitrosn assoaciada à tomografia computadorizada (PET/CT) e composição corporal - Josiane Monteiro Almeida (2022)
Introduction: Positron emission tomography in combination with computed tomography (PET/CT) is an important tool for the diagnosis and staging in oncology, and can provide important information about the body composition and the nutritional status of individuals with cancer. Objectives: To evaluate the relationship between the values of hepatic and tumor uptake of 18FDG obtained by PET/CT with body composition quantified by CT in cancer patients. Methods: Cross-sectional study, in which the values of hepatic (SUV mean hepatic) and tumoral (SUV maximum tumoral) of 18FDG obtained by PET/CT were related to body composition analysis provided by CT images. Other markers of body composition, nutritional status and functionality were also evaluated. Individuals aged over 18 years, of both sexes, with suspected or diagnosed cancer who underwent PET/CT at the request of the attending physician were included. Results: One hundred and fifty-four patients, with a median age of 60.5 years, 84 elderly and 70 adults were assessed. Most of them (78.6%) had a diagnosis of solid neoplasm, and 34% of the patients were classified instage IV. The median weight, skeletal muscle mass, muscular, visceral and subcutaneous adipose tissue, muscle radiodensity (SMD) and skeletal muscle index (SMI) were respectively 70.8kg (61.1 - 80.0kg), 121.1cm² (102 .8 – 144.3cm², 6.3 cm² (3.7 – 8.9cm²), 99.9 cm² (61.9 – 179.1cm²), 165.8 cm² (106.1 – 228.9 cm²), 36.6 HU (30.6 – 41.7 HU) and 44.1 cm²/m² (39.1 – 51.2 cm²/m²). Women had lower SMI values [40.8 cm/m² (37, 2 cm/m² – 46.2 cm/m² )] The median hepatic SUV was 2.3 (2.1 – 2.6) and the median maximum tumor SUV was 4.7 (2.8 – 8, 8) Anthropometric measurements, standardized phase angle, dynamometry and body mass index (BMI) were associated with SMI (p< 0.05). However, only the arm circumference (AC) and calf were associated with the maximum tumor SUV (p< 0.05), and the relationship with the AC was inverse. Individuals classified as having low weight by BMI had a significant correlation between maximum tumor SUV, SMI (rho: -0.624) and SMD (rho: -0.502). Higher values of SMI and SMD were indicative of lower values of maximum tumor SUV in this group (p=0.001 and p=0.015 respectively). The “severely malnourished” group had a lower mean hepatic SUV [2,1 (1,9 – 2,3)] and higher tumor maximum SUV values [7.7 (5.7 - 11.8)]. There was no correlation between SMI and SMD with mean hepatic SUV (p>0.05). The maximum tumor SUV was correlated with the SMI -0.163 (p=0.043), the higher the SMI, the lower the maximum tumor SUV. We did not observe any difference between SMI and maximum tumor SUV when segmented by sex and age (p>0.05). Regarding stage, there was a correlation between SMI and maximum tumor SUV between individuals in stage III and IV -0.277 (p<0.05), higher maximum tumor SUV, lower SMI. Conclusion: Tumor uptake of 18FDG in cancer patients is related to SMI by CT.